Dominica : Interim Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Poverty in Dominica exhibits the following: poor households tend to be larger than nonpoor households; poor households contain proportionately fewer persons of working age, and there is no significant difference in the gender distribution of poverty in the country. The challenges of this poverty-reduction strategy will be to foster growth and private sector employment, and to achieve fiscal and broader economic stability and a dynamic, accountable, and effective public service to provide a strong basis for the sustainable and integrated political, social, and economic development of Dominica.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet